Peran Workplace Well-being terhadap Mental Health: Studi pada Karyawan Disabilitas - F Fridayanti; N Kardinah; Tyas Julianti Nurul Fitri (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2019)
Disability employees are still relatively few employed in he company. When disability employees have to work in tandem with normal employees, of course there will be a little different treatment from their normal coworkers. It will have a impact on psychological conditions especially on mental health and workplace well-being disability employee, both in internal and external factors. This study examined the effect of workplace well-being on mental health. The study was conducted at one company located in Garut, West Java. Total participants are 70 employee with disability (30 men and 40 women). The researcher used a workplace well-being Questionaire and General Health Questionare (QHG). Data were analyzed using simple regression analysis. The results showed that there was an effect of workplace well-being on mental health. It can be seen from the significance value of 0,000 less than 0.005.